Re-reading Foucault. - Golder, Ben (Taylor and Francis, 2012)
Law, Rights and Power: Re-Reading Foucault is the first collection in English to fully address the relevance of Foucault's thought for law. Michel Foucault is the best known and most cited of the late twentieth-century's 'theory' academics. His work continues to animate a range of different critical work across intellectual disciplines in the arts, humanities and social sciences. There has, however, been relatively little examination of the legal implications and applications of Foucault's work. This book fills that gap, providing an in-depth analysis of Foucault's thought as it pertains to t.